A CT Radiologic Assessment of the Incidence of Cochlear–Facial Dehiscence and the Thickness of Bone between the Cochlea and Facial Nerve among Normal Temporal Bones - Nayeri, Diba; Gopen, Quinton (Journal of Neurological Surgery Part B: Skull Base, 2024)
Cochlear–facial dehiscence (CFD) is a relatively new diagnosis which occurs when the bony partition between the labyrinthine segment of the facial nerve and the cochlea is dehiscent. This is considered one of several third window lesions which produce varying degrees of auditory and vestibular symptoms. Imaging studies have identified a consistently higher incidence of CFD when compared with the only histopathologic study present in the literature. This research effort adds to the literature using uniform computed tomography scan images across over 226 ears (114 patients) to identify the radiographic incidence of CFD in normal patients without ear pathology or symptoms. This study identified an incidence of 18.1% of the ears analyzed having dehiscence without any correlation to age or gender. When dehiscence was not identified, the mean thickness of bone between the cochlea and the facial nerve was 0.60 ± 0.24 mm.
Keywords: cochlear–facial dehiscence; CFD; third window lesions; cochlea; facial nerve; temporal bone